ISOLATION AND SCREENING OF AMYLASE PRODUCING BACTERIA FROM PALM OIL LIQUID WASTE - Harmileni Harmileni; Rika Silvany; Tengku Rachmi Hidayani; Edy Fachrial (JBIO: jurnal biosains (the journal of biosciences), 2022)
Amylase is the most studied enzyme in biotechnology and also accounts for 25% of the total enzyme market worldwide. In industry, amylase has potential applications in the bakery, textile, detergent, syrup, pharmaceutical, and medical industries. One of the potential sources of amylase is microbes, because it is easy to isolate, culture, and also genetically engineered. Liquid waste is one of the most potential and abundant sources of microbes. In this study, the authors used palm oil waste as a source of amylase-producing microbes. The purpose of this study was to isolate and screen bacteria that showed amylase activity. Bacteria were isolated from palm oil liquid waste samples using the serial dilution method and the number of CFUs was calculated. The isolates were then characterized morphologically including Gram staining, elevation, color, edge, cell shape and also catalase reaction. Characterization results obtained 7 gram positive isolates and 8 gram negative isolates, the shape of cocci (12 isolates) and bacilli (3 isolates) and convex elevation and white isolates. Amylase activity was detected using nutrient agar media supplemented with 1% starch and the amylolytic index was measured. Amylolytic activity was indicated by the presence of a clear zone around the isolate. Of the 15 isolates, only 1 isolate showed amylase activity, namely LCF 4 with an amylolytic index of 0.57. Further research is recommended to identify and determine enzyme activity.Keywords : Activity; amylase; bacteria; palm oil liquid waste